2007
DOI: 10.1002/chem.200700554
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids for Soft Functional Materials with Carbon Nanotubes

Abstract: A serendipitous finding that ionic liquids gel with carbon nanotubes has opened a new possibility of ionic liquids as modifiers for carbon nanotubes. Upon being ground into ionic liquids, carbon nanotube bundles are untangled, and the resultant fine bundles form a network structure. This is due to the possible specific interaction between the imidazolium ion component and the pi-electronic nanotube surface. The resultant gelatinous materials, consisting of highly electroconductive nanowires and fluid electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
313
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(321 citation statements)
references
References 106 publications
7
313
0
1
Order By: Relevance
“…Our previous studies showed that surfactants and ionic liquids, such as alkylimidazolium salts, effectively improved the dispersion of zinc oxide nanoparticles in the elastomer [6]. Fukushima and Aida [8] reported that imidazolium ionic liquids can be used to disperse single-walled carbon nanotubes in soft composite materials. The ability of ionic liquids to functionalise and improve the dispersion of carbon nanotubes has been intensively studied [9,10] also in diene elastomers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that surfactants and ionic liquids, such as alkylimidazolium salts, effectively improved the dispersion of zinc oxide nanoparticles in the elastomer [6]. Fukushima and Aida [8] reported that imidazolium ionic liquids can be used to disperse single-walled carbon nanotubes in soft composite materials. The ability of ionic liquids to functionalise and improve the dispersion of carbon nanotubes has been intensively studied [9,10] also in diene elastomers [11].…”
Section: Introductionmentioning
confidence: 99%
“…Technological developments of so called 'smart' materials are continuously boosting over the whole past decade [1][2][3][4][5][6][7]. Materials are classified as 'smart' if they possess an intrinsic ability to sense and definitely to respond to various external stimuli in a predictable way ( [2] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The research of these features open new technological vista for various sensors, molecular machines, switches, controllers, etc. Ionic liquids (ILs), or sometimes specifying more precisely -room temperature ionic liquids (RTILs), which, according to definition, are compounds consisting entirely of ions, but in contrast to 'traditional' salts they are liquids already at, or close to, room temperature [8,9], are widely and successfully applied creating multifunctional materials and compositions [3][4][5][6][7]. Selecting combinations of anionic and cationic subsystems one can alter defined physical and chemical properties of RTILs getting possibilities to sense and to control various molecular processes in these media.…”
Section: Introductionmentioning
confidence: 99%
“…Imidazoliumbased ILs could support the exfoliation of CNT bundles in the process leading tostable gel-like products. [77,78] The same approach has been employedfor IL monomers in order to synthesize solid composites or polymeric gels. Moreover, CNT dispersions stabilized by PILs could be reversibly transferred from water to organic solvents.…”
Section: Introductionmentioning
confidence: 99%